Gen Z's Perception of Ideal Work Culture in School Environment - Wiranata, Rz. Ricky Satria (Institut Agama Islam Ma`arif NU (IAIMNU) Metro Lampung, 2024)
Work culture is a crucial issue in the world of education, considering the still rampant cases of teachers resigning (turnover) due to a less than ideal work environment. This condition can have serious impacts, such as a shortage of teaching staff, an increase in the ratio of students to teachers, and a decrease in the quality of learning. This study aims to map Gen Z's perceptions of the ideal work culture in the school environment. The subjects of the study were students of the Islamic Education Management Study Program (MPI) of STAI Terpadu Yogyakarta who had participated in educational internships at Islamic educational institutions. The approach used was phenomenology, data collection techniques through open surveys based on Google Form. Data analysis was carried out using NVivo 12 software, data validity testing through peer debriefing techniques. The results of the study showed that Gen Z's main priorities in an ideal work culture are comfort including clear communication, a collaborative environment, flexibility, life balance (mental) and rejecting the hierarchy of superiors and subordinates (embracing each other). Gen Z also wants career development through various self-development and technology adaptations. In addition, the aspect of appreciation is also important, both in the form of verbal appreciation and real incentives. Modern facilities are an attraction for Gen Z, while salary is also important for Gen Z but is not the main priority in showing loyalty and performance to the institution. This finding is important as a reference for curriculum development in universities and educational institutions' strategies in creating a work culture that suits the characteristics of Gen Z.